Pengembangan Kompetensi Digital Mahasiswa Magang MBKM melalui Program Magang di Kantor Badan Kepegawaian Daerah Provinsi Kalimantan Tengah - M. Azhary; Nurul Hikmah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This article examines the development of students' digital competencies through the Merdeka Belajar – Kampus Merdeka (MBKM) Internship Program at the Regional Civil Service Agency (BKD) Office of Central Kalimantan Province. The MBKM policy aims to improve student competencies through flexible learning outside the campus, including internships that bridge the academic theory of the Islamic Education Management Study Program with workplace practices. The research method used a task-based participatory approach over a period of 4 months (July-November 2023), with intensive guidance from BKD staff and academic advisors, focusing on documenting routine activities, multimedia editing, and content production for social media. The results show that students successfully documented 12 morning assemblies, 8 morning exercises, and more than 15 BKD Head events, as well as educational content such as the “ASN Berakhlak” series published on Instagram @bkdprovkalteng, increasing the engagement rate through editing with Canva. The discussion emphasized the effectiveness of link and match in developing digital skills, creativity, and resilience, supported by relevant research references. The conclusion stated that this program was effective in preparing graduates for work, with recommendations for expanding digital ethics training and broader collaboration. This article contributes to the understanding of MBKM practices in local government agencies.